Assessment of cytocompatibility and mechanical properties of detergent-decellularized ovine pericardial tissue. Issue 11 (November 2019) - Mogaldea, Alexandru; Theodoridis, Karolina; Goecke, Tobias; Tudorache, Igor; Haverich, Axel; Cebotari, Serghei; Hilfiker, Andres
Background: Autologous pericardium is widely used for the repair of different sized cardiovascular defects. However, its use is limited especially in redo cardiac surgery. We developed an engineered tissue based on decellularized pericardium reseeded with blood-derived endothelial cells. Materials and Methods: Decellularization of ovine pericardium was performed using detergent treatment. Ovine outgrowth blood-derived and green fluorescent protein–labeled endothelial cells were used to reseed the decellularized ovine pericardium on the mesothelial side. The cell adhesion was assessed using fluorescent microscopy up to 15 days of in vitro cultivation. The mechanical properties of the pericardium were evaluated using suturability, burst pressure, and suture retention strength tests. Results: After decellularization the pericardial sheets appeared cell-free and repopulation using ovine blood-derived endothelial cells was successful by forming a robust monolayer. Detergent treatment did not affect the extracellular matrix. The thickness of decellularized tissue was similar to native ovine pericardium (285.3 ± 28.2 µm, respective 276.9 ± 23.8 µm, p  = 0.48). Decellularized patch showed similar suturability comparable to the native ovine pericardium. Resulted burst pressure was not significantly different (native/decellularized: 312.5 ± 13.6/304.2 ± 16, p  = 0.35). The suture retention strength of native pericardium was 638.33 ± 90.2 gr and comparable to decellularized tissue (622.2 ± 89.9 gr, p  = 0.76). No differences were observed concerning elongation of native and decellularized pericardium (8.33 ± 1.5 and 8.5 ± 0.84 mm, respectively; p  = 0.82). Conclusion: Mesothelial surface of decellularized ovine pericardium is suitable for reseeding with ovine blood-derived endothelial cells. The mechanical properties of detergent-treated pericardium were comparable to native tissue.